Insights of roles played by septins in pathogenic fungi. Issue 1 (1st January 2021) - Li, Lin; Zhu, Xue-Ming; Su, Zhen-Zhu; Del Poeta, Maurizio; Liu, Xiao-Hong; Lin, Fu-Cheng
ABSTRACT: Septins, a conserved family of GTP-binding proteins, are widely recognized as an essential cytoskeletal component, playing important roles in a variety of biological processes, including division, polarity, and membrane remodeling, in different eukaryotes. Although the roles played by septins were identified in the model organism Saccharomyces cerevisiae, their importance in other fungi, especially pathogenic fungi, have recently been determined. In this review, we summarize the functions of septins in pathogenic fungi in the cell cycle, autophagy, endocytosis and invasion host-microbe interactions that were reported in the last two years in the field of septin cell biology. These new discoveries may be expanded to investigate the functions of septin proteins in fungal pathogenesis and may be of wide interest to the readers of Microbiology and Molecular Pathology.